Avaliação do Impacto de uma Intervenção em Gestão de Stress em Pacientes com Fadiga Oncológica a Realizar Radioterapia: Resultados Preliminares - Deep, Cláudia Ng; Leal, Isabel; Patrão, Ivone (Psychology, community & health, 2012)
Aim: We present the preliminary results of the assessment of the impact of cognitive-behavioral intervention on stress management (CBISM) on patterns of emotional regulation (anxiety, depression and stress) and resilience in patients with cancer fatigue and in radiotherapy. Method : We compare the results between the control group (20 participants subject to the conventional treatment of radiotherapy without CBISM) and the experimental group (20 participants subjected to the treatment of conventional radiotherapy with CBISM) in 2 times: at the beginning and end of radiotherapy. We used: a Demographic Questionnaire, a Scale of Anxiety, Depression and Stress, a Scale of Resilience as well as the Emotion Thermometers. Results : There is a significant fall of anxiety, depression and stress, ( p < .005) in the experimental group (not in the control group), as well as the significant rise of global resilience ( p < .005) and its constituents. Conclusion : The results indicate significant differences between both groups and both times, stressing the effectiveness of CBISM. [PUBLICATION ABSTRACT]